Educação rural na Paraíba (1946-1961): um meio para fixar o homem ao campo - Pereira, Priscilla Leandro (2013)
This study falls within the field of History of Education, more specifically in the field of research about the history of rural education.Aims to analyze the educational projects and Brazilian Paraiba intended for rural areas, in terms of its importance in the national context, in the period 1946-1961.This time frame has as reference the year of publication of the Organic Law of Agricultural Education and the second, the promulgation of the Law of Guidelines and Bases of National Education, two legal frameworks in the context of public policies in education.Accordingly, we seek to further analyze this study rural education in Paraíba, discussing about the educational activities for rural areas that reverberated almost always in the discourse of the need to fix the man inside and keep it tied to the land.Therefore, we work with all types of sources having as main one newspaper A União , besides the posts of presidents and governors, laws, decrees, among other photographs, as well as the literature review on the topic.For that, we do key readings from the works of Castro (1997), Pinheiro (2002), Saviani (2008), Werle (2010), Faria Filho (2011), among others. The research was conducted with reference to the ideas of Hobsbawm (1998) to address the continuities and discontinuities of the historical process and Gramsci (1995 and 1998), especially in regard to the role of intellectuals as organizers of culture.Thus, we believe that education rural Paraiba, in this period, was the target of a concern more strongly by public managers, however, there was a full adherence to a specific model of school, since the pedagogical models remained subordinate to the curriculum urban. However, to fill this gap and try to "fix the man in the field" were released a series of teaching aids rural institutions, such as the educational film and radio, clubs agricultural weeks of large farmers, the rural missions and campaigns against illiteracy, who acted in a timely manner about the issues involved in the organization of education and rural education. However, all of these actions have not gone strategies that the power structure (government, church and landowners) used to circumvent or minimize social tensions and conflicts caused by the way the occupation and use of land. This problem interfered, and even interfere in the full development of rural education, namely: non-fulfillment of the agrarian reform.